BLADDER LEIOMYOMA - CASE-REPORT AND REVIEW OF THE LITERATURE - Goldberg, José [UNESP]; Amaro, João Luiz [UNESP]; Vercesi, L.; Trindade, JCS (Masson Editeur, 1994)
Mesodermal tumors of the urinary tract are anusual, being leiomyoma the most frequent tumor type. We present a case of leiomyoma of the urinary bladder in a 29 year old woman and review the literature. Clinical features, diagnosis and treatment are discussed.
Keywords: LEIOMYOMA; BLADDER; MESODERMAL TUMOR